From the "Culture of Death" to the "Crisis of Liberalism": Recent Shifts in Catholic Politics - McCabe, Kevin P. (Journal of religion & society. Supplement, 2021)
This article identifies and assesses some of the shifts that have occurred in conservative Catholic politics in the United States over the last twenty years. For much of the late 1990s and early 2000s, a politics focused on denouncing “the culture of death” predominated in U.S. conservative Catholicism. In recent years, this political and religious framework has lost ground to a politics addressing “the crisis of liberalism.” I examine this new political agenda by looking at two of its leading exponents, journalist Sohrab Ahmari and political theorist Patrick Deneen. The article closes by raising three points for consideration regarding the relationship between the critique of liberalism and the magisterium of the Catholic Church, the place of LGBTQ persons in the critique of liberalism, and what this means for the future of politics in the Church in the United States.